Diet and history of infectious diseases affect the incidence of anemia in adolescent girls - Turrahmi, Hirfa; Rahayu, Heti; Fitria, Khaulah (Universitas 'Aisyiyah Yogyakarta, 2024)
This study was conducted at SMPN 77 Central Jakarta in 2023 to determine the correlation between diet, physical activity and history of infectious diseases with the incidence of anemia in adolescent girls. The research method used is correlative descriptive with a cross-sectional design. The research sample was 114 adolescent girls who were selected by stratified random sampling technique. The results showed that as many as 36.8% of adolescent girls experienced anemia, with a total of 43.0% having a LILA (Upper Arm Circumference) <19 cm. The results of statistical analysis showed that there was a correlation between diet and the incidence of anemia (p=0.000) and OR=53.3 (CI 95%. 6.7 – 420.3) as well as disease history with the incidence of anemia (p=0.000) and OR=17.9 (CI 95%. 6.3 – 50.6). However, no association was found between physical activity and the incidence of anemia (p=0.537). The results of the study concluded that adolescents with poor diets had a 53.3 times greater risk of developing anemia, while adolescents with a history of infectious diseases had a 17.9 times greater risk. This study suggests that adolescents regulate their diet by paying attention to the frequency and type of food consumed and maintaining immunity to avoid infectious diseases and prevent anemia by consuming iron tablets regularly.